ANTIBIOTIC RESISTANCE PATTERN AGAINST VARIOUS ISOLATES OF STAPHYLOCOCCUS AUREUS FROM MILK PRODUCTS KHOYA AND BURFI - Farzana, Kalsoom; Shah, Syed Nisar Hussain; Jabeen, Farzana; Batool, Shazia (Journal of Research (Science), 2004)
A total of twenty eight samples of each khoya and burfi were taken from different shops in Multan. All the samples were found to be contaminated with Staphylococcus aureus. When these S. aureus isolates from burfi were subjected to various antibiotic, lincomycin, tetracycline, cephradine and co-trimaxazole sensitivity tests, were found to be 100% effective against S. aureus. The decreased order of susceptibility of other antibiotics (amoxil, amikin, augmentin, ampiclox, erythromycin, ampicillin and colistin) was 96.43%, 96.43%, 92.86%, 82.14%, 89.29%, 28.57% and 7.14%, respectively for S. aureus isolates from burfi. The increased order of susceptibility of S. aureus against various antibiotics collected from khoya samples were colistin (14.29%), ampicillin (17.86%), ampiclox (71.43%), tetracycline (75%), .erythromycin and lincomycin each (89.29%), amikin and co-trimaxazole each (92.86%), cephradine and augmentin each (96.43%). It can be concluded that hygiene of milk products is poor and resistant strains might have contaminated these products during the process of transportation or preparation.